Burnout among music education student in Faculty of Music UiTM Shah Alam / Nurul Adila Mohd Roshidi - Mohd Roshidi, Nurul Adila (Faculty of Music, 2017)
Burnout is a syndrome of emotional exhaustion and cynicism that occurs frequently among individuals who do cpeople-work' of some kind. A key aspect of the burnout syndrome is increased feelings of emotional exhaustion. Another aspect is the development of negative, cynical attitudes and feelings about one's clients. A third aspect of the burnout syndrome is the tendency to evaluate oneself negatively, particularly with regard to one's work with clients. This study aims to identify the level and factors that may contribute to burnout among 50 UiTM music education students. Subjects were asked questioned using a 4 set of survey that cover number of subjects and credit hours in this semester, burnout, time management and workload. Implications for music education and future research are discussed.